Ibuprofen and acetaminophen: effect on muscle inflammation after eccentric exercise - Peterson, J. M.; Trappe, T. A.; Mylona, E.; White, F.; Lambert, C. P.; Evans, W. J.; Pizza, F. X. (Medicine & Science in Sports & Exercise, 2003)
PURPOSE: We examined the influence of ibuprofen and acetaminophen on muscle neutrophil and macrophage concentrations after novel eccentric contractions. METHODS: Twenty-four males (25 +/- 3 yr) were divided into three groups that received the maximal over-the-counter dose of either ibuprofen (1200 mg x d-1), acetaminophen (4000 mg x d-1), or a placebo after eccentric contractions of the knee extensors. Biopsies from the vastus lateralis were taken before and 24 h after exercise. Inflammatory cells were quantified in muscle cross-sections using immunohistochemistry. RESULTS: Macrophage concentrations were elevated by 1.5- to 2.5-fold (P < 0.05) at 24 h postexercise relative to preexercise concentrations, whereas neutrophil concentrations were not significantly elevated. Muscle inflammatory cell concentrations were unaffected by treatment with ibuprofen or acetaminophen when compared with placebo. CONCLUSIONS: Maximal over-the-counter doses of ibuprofen or acetaminophen, when administered therapeutically, do not affect muscle concentrations of neutrophils or macrophages 24 h after a novel bout of eccentric contractions.